Three-Dimensional Carbon-Supported MoS2 With Sulfur Defects as Oxygen Electrodes for Li-O2 Batteries - Liu, Yun; Zang, Yipeng; Liu, Xinmiao; Cai, Jinyan; Lu, Zheng; Niu, Shuwen; Pei, Zhibin; Zhai, Teng; Wang, Gongming (Frontiers in Energy Research, 2020)
Recently, Li-O2 batteries have been considered to be promising next-generation energy storage devices owing to their high theoretical specific energy. However, due to the sluggish reaction kinetics of oxygen conversion, practical applications cannot achieve the desired results. By introducing vacancies in the MoS2 basal plane and using an in-situ synthesis method, we demonstrated the excellent catalysis of MoS2−x for oxygen redox kinetics, which can improve Li-O2 battery performance. The prepared MoS2−x displays little polarization, with a potential gap of 0.59 V and a high discharge capacity of 8,851 mA h g−1 at a current density of 500 mA g−1. The improved performance is mainly attributable to abundant S defects and plentiful diffusion channels in the MoS2−x/carbon 3D structural cathodes, which enable the adsorption of gaseous oxygen, reaction intermediates, and discharge products. To the best of our knowledge, these structures fabricated through 3D network design and surface modulation are among the best oxygen conversion catalysts developed so far, offering a new vista for the design of Li-O2 catalysts and beyond.